Role of the gut microbiota in complications after ischemic stroke - Zhang, Jinwei; Ling, Ling; Xiang, Lei; Li, Wenxia; Bao, Pengnan; Yue, Wei (Frontiers in Cellular and Infection Microbiology, 2024)
Ischemic stroke (IS) is a serious central nervous system disease. Post-IS complications, such as poststroke cognitive impairment (PSCI), post-stroke depression (PSD), hemorrhagic transformation (HT), gastrointestinal dysfunction, cardiovascular events, and post-stroke infection (PSI), result in neurological deficits. The microbiota-gut-brain axis (MGBA) facilitates bidirectional signal transduction and communication between the intestines and the brain. Recent studies have reported alterations in gut microbiota diversity post-IS, suggesting the involvement of gut microbiota in post-IS complications through various mechanisms such as bacterial translocation, immune regulation, and production of gut bacterial metabolites, thereby affecting disease prognosis. In this review, to provide insights into the prevention and treatment of post-IS complications and improvement of the long-term prognosis of IS, we summarize the interaction between the gut microbiota and IS, along with the effects of the gut microbiota on post-IS complications.